Analysis of improved low cost transmissive formaldehyde (CH2O) ultraviolet gas sensor - Mohamad Shahrulnizam, Zakaria; Mohd Rashidi, Salim; Mohd Haniff, Ibrahim; Asrul Izam, Azmi; Ahmad Sharmi, Abdullah; Muhammad Yusof, Mohd Noor; Nor Hafizah, Ngajikin; Hadi, Manap (Universiti Teknologi Malaysia, 2017)
The Ultraviolet gas sensor specifically designed for Formaldehyde (CH2O) which consists of low cost components has been simulated using ZEMAX®12. The transmissive gas cell design used aluminum material that is robust and inert material to increase its performance. CAF2 lens has been replaced with CAF2 window to reduce the construction cost. Therefore, to collimate the light, compound parabolic concentrator (CPC) structure attached at both ends of the gas cell. The simulated results show the improved gas cell with CAF2 windows and truncated CPC structure yields the initial power efficiency of 60.72%. However, when the optical path length of the gas sensor being adjusted and reduced down to 25 mm, the power efficiency increases to 66.82% with peak irradiance and output power of 0.2511 W/cm2 and 0.2673 mW respectively.